OPTIMALISASI RADAR ABU TERBANG PADA BETON DENGAN AGREGAT KASAR RINGAN DARI LEMPUNG BEKAH - Tanudjaja, Hanock
Indonesia have several variation of natural resources which depend on the condition of soil. Some areas contain of soft soil structure with low bearing capacity so that it is better to have light buildings on these areas. There are another areas where no gravels or natural stones that can be used as aggregate for concrete. So, the use of Artificial Light- Weight Aggregate (ALWA) can be an alternative solution. In C i i . p , has been built a factory that produces light-weight aggregate made from expanded clay. At the beginning this aggregate is used for hidrofonics and bricks. Because this kind of aggregate is light, there is a thought to use it as coarse aggregate for light concrete mixture for building structure. From the result of this concrete research with cement mixture composition type I, coarse aggregate ALWA from Cilacap, sand, water, with or without fly ash from PLTU Suralaya and with or without superplasticizer has unit weight range as 1750-1850 kg/ms. This result shows that this concrete can be categorized as light-weight concrete ( LWC). By substituting the fly ash partially in the concrete mix, the portion of cement could be reduced. From the fly ash content which is studied and tried in this research (0%, 8%, 12%, 16%, 20% and 24% from cement weight), 16% is the optimum content. With superplasticizer as addition material about 2% in this concrete composition the increase of strength are obtained. The light weight concrete characteristic with ALWA mentioned above is obtained through compressive strength, tensile strength, modulus of rapture or fracture resistance, modulus of elasticity, poisson\'s ratio, and micro slawtare test.